An ontology network to support knowledge representation and semantic interoperability in the HCI domain - Costa, Simone Dornelas (2022)
Human-Computer Interaction (HCI) is a multidisciplinary knowledge area aimed at the practice of information technology centered on humans. Currently, increasingly interactive systems are required to be personalized, responsive, adaptive, user-friendly, and characterized by increasingly connected environments and intelligent applications. Being such a diverse area, HCI involves a diverse body of knowledge and a complex set of concepts. This leads to semantic interoperability problems, which affect users, designers, and interactive systems. Moreover, the design and evaluation of interactive systems are knowledge-intensive activities. In this context, knowledgerelated problems, such as the ones related to knowledge representation and sharing, cause the risk of losing relevant knowledge. Therefore, efficient mechanisms to promote common understanding and collective construction of knowledge are necessary. Ontologies have been successfully used in several domains to capture and organize knowledge seeking to deal with interoperability and knowledge-related problems. In this work, we argue that organizing HCI ontologies in an ontology network provides a comprehensive conceptualization of the HCI domain; favors knowledge growth, reuse, and integration; and potentializes the use of ontologies in knowledgebased and interoperability solutions. In this sense, this work proposes the Human-Computer Interaction Ontology Network (HCI-ON). HCI-ON is grounded on a foundational ontology, is aligned with HCI standards and literature, and addresses HCI relevant aspects. HCI-ON has a core ontology that addresses the human-computer interaction phenomenon and domain-specific ontologies covering HCI subdomains such as HCI design, evaluation, and user interface, among others. Aiming at knowledge growth in a consistent way, HCI-ON provides mechanisms to support its constant evolution throughout the addition of new or existing ontologies. In the HCI domain is possible to use HCI-ON as a whole or extracts of it to solve semantic interoperability and knowledge-related problems. To demonstrate the use of HCI-ON to support solving such problems, we used an HCI-ON extract to develop UXON, a system that supports UX evaluation based on interaction logging produced by an immersive application called Compomus. As a result, the use of HCI-ON was considered feasible and useful.